ONLINE DISPUTE RESOLUTION AND JUSTICE SYSTEM INTEGRATION: BRITISH COLUMBIA’S CIVIL RESOLUTION TRIBUNAL - Salter, Shannon (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2017)
This article undertakes a brief comparison of private and public online dispute resolution [ODR] systems before providing an overview of the Civil Resolution Tribunal [CRT], Canada’s first online tribunal, and its ODR processes. The article discusses why the CRT has come to be, how it has been implemented, as well as its implications for civil justice reform more broadly. A main proposition is that the transformational potential of ODR will only be realized when ODR is fully integrated with public justice processes. This proposition is not without its difficulties, as the CRT’s experience illustrates. To this end, the article also provides an introduction to some of the opportunities and challenges offered by an integrated ODR system like the CRT as well as some of the steps the CRT has taken to meet these demands as transparently and collaboratively as possible.